Effectiveness and acceptability of metformin in preventing the onset of type 2 diabetes after gestational diabetes in postnatal women: a protocol for a randomised, placebo-controlled, double-blind feasibility trial — Optimising health outcomes with Metformin to prevent diAbetes After pregnancy (OMAhA) - Doris Lanz; Julie Dodds; Khalid Khan; Graham Hitman; Elena Pizzo; Shakila Thangaratinam; John Robson; Chiamaka Esther Amaefule; Angeliki Bolou; Zoe Drymoussi; Francisco Jose Gonzalez Carreras; Maria del Carmen Pardo Llorente; et al. (BMJ Open, 2020)
Introduction Up to half of all women diagnosed with gestational diabetes mellitus develop type 2 diabetes within 5 years after delivery. Metformin is effective in preventing type 2 diabetes in high-risk non-pregnant individuals, but its effect when commenced in the postnatal period is not known. We plan to assess the feasibility of evaluating metformin versus placebo in minimising the risk of dysglycaemia including type 2 diabetes after delivery in postnatal women with a history of gestational diabetes through a randomised trial.Methods and analysis Optimising health outcomes with Metformin to prevent diAbetes After pregnancy (OMAhA) is a multicentre placebo-controlled double-blind randomised feasibility trial, where we will randomly allocate 160 postnatal women with gestational diabetes treated with medication to either metformin (intervention) or placebo (control) tablets to be taken until 1 year after delivery. The primary outcomes are rates of recruitment, randomisation, adherence and attrition. The secondary outcomes are maternal dysglycaemia, cost and quality of life outcomes in both arms, and acceptability of the study and intervention, which will be evaluated through a nested qualitative study. Feasibility outcomes will be summarised using descriptive statistics, point estimates and 95% CIs.Ethics and dissemination The OMAhA study received ethics approval from the London-Brent Research Ethics Committee (18/LO/0505). Trial findings will be published in a peer-reviewed journal, disseminated at conferences, through our Patient and Public Involvement advisory group (Katie’s Team) and through social media platforms.Trial registration number ISRCTN20930880